Anticancer Uses of Medicinal Plants in Turkish Traditional Medicine - BOZYEL, Mustafa Eray; MERDAMERT BOZYEL, Elif; CANLI, Kerem; ALTUNER, Ergin Murat (KSU Journal of Agriculture and Nature, 2019)
The use of plants as therapeutic agents have been known since the ancient times. In developing countries, traditional medicinal plants are critical for disease treatment. Various herbal drugs  are obtained from these plants for therapeutic use. These herbal drugs are used in the treatment of many diseases from diabetes to cancer. Today, cancer is one of the most important life-threatening diseases for human. Some of the methods used in the treatment of cancer  include herbal sources. The scientific world  is not oblivious to many herbal drugs used for cancer in traditional treatment methods. Due to the limited effectiveness of drugs, an increasing number of studies have been conducted in the last decade to increase the success of cancer treatments. In recent years, the importance given to the herbal drugs used for medicinal purposes and the studies on the medicinal uses of plants have  increased in our country. In this review, researches about the herbal drugs traditionally used against cancer by the local people were investigated. As a result of the study, 160 plant taxa and 17 multi-herbal formulas were reported for cancer treatment in Turkish traditional medicine.
Keywords: Yapısal Biyoloji; Anticancer; Medicinal plants; Herbal drugs; Multi-herbal formulas; Turkish traditional medicine; Structural Biology; Antikanser; Tıbbi bitkiler; Bitkisel ilaçlar; Çoklu-bitkisel formüller; Türk geleneksel tıbbı; 2. Zero hunger; 1. No poverty; 15. Life on land; 3. Good health